Opportunities and challenges faced in international sport participation: Migration motivations and leisure constraints of United States athletes when playing professional volleyball games in South Korea - Suh, Y. I.; Kim, J. (Advances in Hospitality and Leisure, 16, 2020)
The primary purpose of this study was to examine the motivation factors associated with American volleyball athletes' migration to Korea and to identify the constraints that interfered with their leisure pursuits away from their primary sport engagement. Using semi-structured in-depth interviews with 12 participants, four themes were identified under migration motivation: (1) career extension and longevity, (2) monetary compensation, (3) cultural experiences, and (4) coach/player recommendations, and three themes under leisure obstacles associated with acculturation: (1) language barrier, (2) lack of time, and (3) limited social networks. This study provides athletes with information on migration motivation and what elements prevent them from thoroughly engaging in leisure participation while they are stationed abroad.